ANALYSIS OF FATTY DEGENERATION OF THE TRAPEZIUS MUSCLE AFTER USE OF ACCESSORY NERVE - Yamauti,Lucas Seiki (2020)
ABSTRACT Objective: To investigate, through magnetic resonance imaging, the occurrence of fatty degeneration of the trapezius in adult patients undergoing nerve transfer procedure, using the spinal accessory nerve. Methods: A total of 13 patients meeting the criteria of unilateral brachial plexus injury and more than one year of postoperative care after nerve transfer surgery underwent an MRI scan of the trapezius. A T1-weighted 3D sequence was used, with the IDEAL technique using 8.0 mm cut thickness, 8.0 mm cut spacing, TR of 100 ms, TE of 3.45 ms, flip angle of 10 degrees, 20 cuts, on the sagittal plane. The images of the upper, transverse and lower parts of the trapezius muscle were then classified according to the degree of fatty degeneration, compared with the contralateral side, using the Goutallier score. Results: For the upper trapezius there was a change of the degeneration state in 23% (p = 0.083), for the transverse section there was a change in 84.6% (p = 0.003), for the lower one there was a change in 92.3% (p = 0.002). Conclusion: The upper trapezius did not undergo significant degeneration after transfer. The lower and transverse trapezius suffered fatty degeneration in most patients, indicating severe functional impairment. Level of Evidence IV, Case series.